Individual interdependence between nocturnal ANS activity and performance in swimmers - Garet, M.; Tournaire, N.; Roche, F.; Laurent, R.; Lacour, J. R.; Barthelemy, J. C.; Pichot, V. (Medicine & Science in Sports & Exercise, 2003)
Purpose: Variations in autonomic nervous system activity (ANS) and variations in performances have been shown to be correlated at the group level in swimmers. The aim of the study was to investigate the strength of that relationship at the individual level.